2020
DOI: 10.31341/jios.44.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Machine Translation System for the Industry Domain and Croatian Language

Abstract: Machine translation is increasingly becoming a hot research topic in information and communication sciences, computer science and computational linguistics, due to the fact that it enables communication and transferring of meaning across different languages. As the Croatian language can be considered low-resourced in terms of available services and technology, development of new domain-specific machine translation systems is important, especially due to raised interest and needs of industry, academia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…One of the problems in machine translation is the lack of training data. This problem was reported by Seljan [17] and Dunder [18,19] for the problem of the automatic translation of poetry with a low-resource language pair. It was reported that the fluency and adequacy of the translation results were skewed to higher scores.…”
Section: Introductionmentioning
confidence: 86%
“…One of the problems in machine translation is the lack of training data. This problem was reported by Seljan [17] and Dunder [18,19] for the problem of the automatic translation of poetry with a low-resource language pair. It was reported that the fluency and adequacy of the translation results were skewed to higher scores.…”
Section: Introductionmentioning
confidence: 86%
“…In the context of the Croatian language and available tools and resources, machine learning has been especially explored with a special focus on machine translation (Dunđer, 2020;Dunđer et al, 2020) and document classification (Dunđer et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Strojno prevođenje istraženo je u raznim domenama, poput poezije (Dunđer i sur., 2020) s posebnim osvrtnom na ljudsku evaluaciju kvalitete strojnog prijevoda (Seljan i sur., 2020). Specijaliziran sustav za automatsko strojno prevođenje za domenu industrije također je razvijen za hrvatski jezik (Dunđer, 2020).…”
Section: Tehnologija Strojnog Prevođenja Za Hrvatski Jezikunclassified